Analyzing Donald Trump’s global warming communication: a polyphonic reading of tweets - Badiang Oloko, Francis (Bergen Language and Linguistics Studies, 2023)
Trump's tweets were part of a mediated public space, seeking to shape public narratives, shout down opponents, and signal the opposition’s non-suitability to carry out the task of governing. He tweeted the phrase “Global Warming” (GW) 100 times from March 2012 to February 2019. Many studies in the fields of communication and political sciences have pointed out Trump’s negative campaigning strategy. His GW communication encapsulates this strategy. Thanks to the linguistic polyphony method, through the ScaPoLine theory, this paper analyzes how Trump positions himself on GW and how he uses it to attempt to damage the reputation of his political opponents in selected tweets.